P91 The development and validation of a polygenic risk score for myocardial infarction in SLE. (23rd March 2020) - Reid, Sarah; Sandling, Johanna K; Alexsson, Andrei; Pucholt, Pascal; Sjöwall, Christopher; Lerang, Karoline; Jönsen, Andreas; Gunnarsson, Iva; Syvänen, Ann-Christine; Troldborg, Anne; Voss, Anne; Bengtsson, Anders A; et al.
Abstract : Background: Patients with SLE have increased morbidity and mortality due to cardiovascular disease. Here, we construct and validate a polygenic risk score (PRS) for myocardial infarction (MI) in SLE. Methods: Patients with SLE (European decent, ≥4 ACR-criteria) were genotyped using a 200K Immunochip SNP array (discovery cohort, Sweden, n=776) and custom MassARRAY assays (replication cohort, Norway/Denmark, n=890). In the discovery cohort, 57 SNPs with previously established association with SLE development (p<5.0×10 -8 ) were investigated for associations with MI using a cox regression model. Significant SNPs were included in a PRS, weighted by their ORs for MI development. The PRS was subsequently validated in the replication cohort. Results: Four SLE-risk genes were found to be associated with a decreased time until the first MI; PTPN22 (OR 1.61, p=0.041), NCF2 (OR 2.47, p=2.1×10 -3 ), STAT4 (OR 1.66, p=5.2×10 -3 ) and IL12A (OR 1.45, p=0.047) and were included in a PRS. The PRS was associated with a higher cumulative prevalence of MI in both the discovery cohort (p=1.1×10 -5, fig 1A) and replication cohort (p=7.7×10 -3, fig 1B). Exploring the PRS further in the replication cohort, patients in the high, compared to the low, PRS-quartile were more often male (p=1.3×10 -3 ), and displayed higher prevalence of the ACR-1982 nephritis and immunological criteria (p=4.1×10 -4 and p=0.036) (fig1C). Analyzing combinations of the identified SNPs, we found the prevalence of MI to be further increased in patients homozygous for both NCF2+STAT4 (pdiscovery =1.6×10 -3, preplication =0.015) or STAT4+IL12A (pdiscovery =3.0×10 -5, preplication =0.036) (fig1D). Conclusion: A high polygenic risk score for MI in SLE is associated with an increased prevalence of myocardial infarction. If confirmed in prospective studies, our results suggest that genetic profiling may be useful for predicting MI in patients with SLE.